Compositionally Complex Doping Enables High-Voltage Spinel Cathodes with Ultrafast Charging and Chemo-Electro-Mechanical Stability - Huize Wu; Chenhao Zhang; Siqi Guan; Pei Tang; Xulin Mu; Yutao Niu; Chunyang Wang; Feng Li (Journal of the American Chemical Society, 2026)
Abstract Next-generation lithium-ion batteries demand high-voltage cathodes that combine exceptional stability with ultrafast charging capability. Cobalt-free spinel-type oxides, owing to their high operating voltage, energy density, and cost effectiveness, are leading candidates, yet their cycle life is still constrained by intrinsic chemo-electro-mechanical instabilities. Here, by leveraging compositionally complex doping, we reconfigure the reaction thermodynamics of a high-voltage spinel cathode by extending its solid-solution regime to higher states of charge, enabling ultrafast charging while maintaining robust chemo-electro-mechanical stability. Multimodal characterization reveals that the reshaped reaction pathway effectively suppresses high-temperature intragranular cracking, interfacial rock salt phase transformation, and parasitic byproduct accumulation, thereby preserving efficient three-dimensional Li+ diffusion. The cathode delivers unprecedented ultrafast-charging durability, achieving 81.8% after 4000 cycles at 10 C (25 °C) and 82.0% after 1000 cycles at 3 C (60 °C). Our work demonstrates that compositionally complex doping can effectively modulate the thermodynamics of phase transformation and enhance the chemo-electro-mechanical stability of high-voltage spinel cathodes, providing new insights into the design of durable fast-charging cathode materials.